Uterine Cancer Mortality in White and African American Females in Southeastern North Carolina. (30th September 2020) - Kravchenko, Julia; Akushevich, Igor; Rhew, Sung Han; Agarwal, Pankaj; Lyerly, H. Kim
Abstract : The residents of southeastern North Carolina (NC) are exposed to multiple socioeconomic and environmental risk factors and have higher mortality rates for a number of diseases. Uterine cancer mortality is known to vary dramatically by race, so we analyzed uterine cancer mortality in populations defined by zip codes in this area to investigate the contributions of various environmental risk factors to race-specific disease patterns. Methods . Zip code specific mortality and hospital admissions for uterine cancer from 2007 to 2013 were analyzed using the NC State Center for Health Statistics data and the Inpatient Database of the Healthcare Cost and Utilization Project datafiles, respectively. Results were adjusted for age, income, education, health insurance coverage, prevalence of current smokers, and density of primary care providers. Results . Uterine cancer mortality rates were generally higher in African American (32.5/100, 000, 95% CI = 18.9–46.1) compared to White (19.6/100, 000, 95% CI = 12.3–26.9) females. Odds ratios (ORs) of uterine cancer death were higher in White females (OR = 2.27, p < 0.0001 ) residing within zip codes with hog concentrated animal feeding operations (CAFOs) (hog density >215 hogs/km 2 ) than in White females residing in non-CAFO communities. African American females living near CAFOs had less pronounced increase of uterine cancer death (OR = 1.08, p = 0.7657 ). Conclusion . White females living in adjacent to hog CAFOs areas of southeastern NC have lower rates of mortality from uterine cancer than African American females, but they have higher odds of death compared to their counterparts living in other NC areas. African American females living near CAFOs also have modest increases from their high baseline mortality. While the observed associations do not prove a causation, improving access to screening and medical care is important to mitigate this health issues in southeastern NC.